Revolutionizing lathe efficiency by bridging theory-practice gaps: Merevolusi efisiensi mesin bubut dengan menjembatani kesenjangan antara teori dan praktik - Budi, Angga Bagus Styo; Mulyadi, Mulyadi (Indonesian Journal of Innovation Studies, 2024)
This study explores the development of a Ball Turning Attachment for lathes to enhance efficiency in manufacturing spherical workpieces. Utilizing materials such as ST 37 and ST 42, the research focuses on the machining processes of milling, drilling, and turning. Despite theoretical estimations suggesting a total work time of 8 minutes 23 seconds, actual implementation records a duration of 12 minutes 23 seconds, highlighting a significant knowledge gap. Experimental procedures conducted in lathe workshops reveal discrepancies between theoretical and actual work times, influenced by factors like feed depth and manual drilling processes. Findings underscore the importance of optimizing tool design and feed rates to improve machining efficiency, offering practical insights for enhancing lathe manufacturing processes and productivity. Highlight: Develop Ball Turning Attachment for lathe manufacturing efficiency. Address discrepancies between theoretical and actual work times. Extract practical insights for enhancing lathe manufacturing processes. Keyword: Lathe manufacturing, Ball Turning Attachment, Machining efficiency, Tool optimization, Experimental procedures